Sociocultural Aspects of Femicide-Suicide: The Case of Israel - Dayan, Hava (Journal of interpersonal violence, 2021)
Among persons who commit murder a certain percentage also commits suicide soon after, a phenomenon known as homicide-suicide. Previous studies indicate that femicide-suicide (female intimate partner homicide-suicides) accounts for the vast majority of homicide-suicide occurrences. Although the femicide-suicide phenomenon cuts across regions and societies, there is a dearth of studies of femicide-suicide patterns, motives, and characteristics among non-Western populations. A review of the few available findings about femicide-suicide in non-Western societies highlights the need for further study and corroboration of the distribution and characteristics of femicide-suicide in non-Western societies. The unique manifestations of the phenomenon among immigrant, ethnic, and social minority groups are of great relevance to Western societies currently facing the challenge of assimilating a growing number of ethnic minorities and immigrant social groups. The study aims to further our understanding of possible sociocultural variations of femicide-suicide by exploring sociodemographic and criminological patterns among non-Western social groups. It presents an analysis of national empirical findings of femicide-suicide across various ethnic and sociocultural groups in Israel in the years 2005-2015, excluding analysis of cases that occurred in Gaza, the West Bank, and East Jerusalem. The characteristics and patterns that are the focus of this study include a sociocultural ethnic profile of the perpetrator, and various criminological characteristics such as homicide and suicide location, homicide and suicide method, and homicide motive. Femicide-suicide events, victims, and perpetrators were compared by calculating frequency distributions and population-based incidence rates. The findings suggest that the distribution of the phenomenon and its criminological characteristics vary across immigrant and ethnic minority groups. Further research is needed to validate the study’s empirical observations and to explore the various manifestations of the phenomenon across non-Western ethnic, social, religious, and cultural groups.